Evaluation of yield and yield components of lamb’s lettuce (Valerianella locusta) grown in thin layer soilless systems - DRAGAN ZNIDARCIC (Smujo International, 2016)
Abstract. Znidarcic D. 2016. Evaluation of yield and yield components of lamb’s lettuce (Valerianella locusta) grown in thin layer soilless systems. Nusantara Bioscience 8: 89-93. Growth and development of lamb’s lettuce (Valerianella locusta L.) have been studied on thin layer soilless systems in plastic greenhouse on the Laboratory field of Biotechnical Faculty, University of Ljubljana. The trial lasted from 23rd of February till 10th of March 2016. The experiment was included cultivar 'Ljubljanski'. Four different substrates have been used: expanded clay aggregate, perlite, vermiculite, and peat. Seedlings were transplanted at distance of 10x10 cm. At the harvest the following parameters were measured: leaves fresh and dry yield, plant height, number of leaves per plant and the nitrate-N content in leaves. The overall effect of the type of substrate on lamb's lettuce growth and yield in the present experiment suggests that the examined materials are suitable substrates for lamb's lettuce soilless cultivation production. The outcomes of the research point to the fact that the lamb's lettuce in perlite treatments brings greater fresh yields compared to the other inert substrates. On the other hand, peat produced higher leaf dry mass as compared to other substrates. A quantitative analysis of the nitrate-N content in leaves showed that the peat is the most effective substrate in terms of low plant nitrate concentration.